Dynamics of Interpersonal Communication Content Writer Radar Jogja 2024 - Isma, Julia Putri Nur; Ratnaningtyas, Rr. Pramesthi (Program Studi Ilmu Komunikasi Fakultas Ilmu Sosial Dan Ilmu Politik Universitas Bandar Lam, 2025)
The dynamics of interpersonal communication in the newsroom environment are evolving along with the increasingly close relationships between individuals involved in the work process. However, this situation did not occur among interns in the Content Writer division of Radar Jogja in 2024. Pre-research observations of the division revealed a lack of openness and mutual support among individuals. Therefore, the purpose of this study is to examine the interpersonal communication of student interns who had difficulty communicating with each other and to determine whether these problems arose from the nature of interpersonal communication within the work environment of the Content Writer division of Radar Jogja. This study applied symbolic interaction theory, which states that humans communicate and exchange meaningful symbols. This study employed descriptive analysis methods, utilizing interviews and observations to collect data based on actual conditions. The results indicated that interpersonal communication among student interns in the Content Writer division of Radar Jogja in 2024 was not optimal, as some students tended to focus on themselves. This led to a lack of openness and mutual support among students, resulting in a lack of closeness.